Pengembangan Sistem Penerangan Jalan Pintar Berbasis IoT dengan Arduino dan NodeMCU - Hidayat, Robi T; Nugroho, Irvan A; Saputra , Duta M W; Marzuki, Marza I; Prayogi, Soni (Jurnal Algoritma, 2024)
The development of this system is to improve energy efficiency and security in urban areas by optimizing the use of street lights based on real-time environmental conditions. The method used involves the design and implementation of hardware and software, where light sensors, motion, and wireless communication modules are integrated with Arduino and NodeMCU. Data from the sensors is used to automatically control the intensity of street lights, adjusting the lighting based on the natural brightness level and the presence of vehicles or pedestrians. Testing was carried out in simulated and field environments to evaluate the performance of the system under various conditions. Key findings from this study indicate that the developed system is able to reduce energy consumption by up to 40% compared to conventional street lighting systems, without sacrificing security. In addition, this system also provides flexibility in managing street lighting through a web-based interface that allows remote monitoring and control. Overall, the development of an IoT-based smart street lighting system with Arduino and NodeMCU has proven effective in improving energy efficiency and security in urban environments. This system offers a practical and widely implementable solution to support sustainable smart city initiatives.